2020
DOI: 10.1017/s0022215120000754
|View full text |Cite
|
Sign up to set email alerts
|

Management of epistaxis in patients on novel oral anticoagulation therapy

Abstract: BackgroundIndividuals on anticoagulation therapy are at increased risk of bleeding, including epistaxis. There is a lack of available reversal agents for novel oral anticoagulation therapy.ObjectiveThis paper reviews the current literature on epistaxis in the context of novel oral anticoagulation use, in order to recommend guidelines on management.MethodA comprehensive search of published literature was conducted to identify all relevant articles published up to April 2019.ResultsPatients on oral anticoagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…The authors reported that it is safe to perform most dental practices in patients taking these anticoagulants regardless of the anticoagulant's discontinuance duration; however, they postulated that dental and maxillofacial procedures requiring graft and osteotomy need at least 24 hours of discontinuance 47 . In cases of severe epistaxis, attempts to reverse anticoagulation or to cease anticoagulant therapy should be considered 48 . Idarucizumab is an antibody antigen-binding fragment that completely reverses the anticoagulant effect within minutes of administration 48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that it is safe to perform most dental practices in patients taking these anticoagulants regardless of the anticoagulant's discontinuance duration; however, they postulated that dental and maxillofacial procedures requiring graft and osteotomy need at least 24 hours of discontinuance 47 . In cases of severe epistaxis, attempts to reverse anticoagulation or to cease anticoagulant therapy should be considered 48 . Idarucizumab is an antibody antigen-binding fragment that completely reverses the anticoagulant effect within minutes of administration 48 .…”
Section: Resultsmentioning
confidence: 99%
“…In cases of severe epistaxis, attempts to reverse anticoagulation or to cease anticoagulant therapy should be considered 48 . Idarucizumab is an antibody antigen-binding fragment that completely reverses the anticoagulant effect within minutes of administration 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antikoagülan kullanımı epistaksis için birçok yayında risk faktörü olarak tanımlanmıştır. [31][32][33] Bizim çalışmamızda AK kullanımı %26 olarak hesaplandı ve AK kullanımı ile hastanede yatış süresi arasında istatistiksel olarak anlamlı bir ilişki bulunamadı. Gomes ve ark.…”
Section: Discussionunclassified
“…Nose bleeds (epistaxis) in older adults have always been associated with significant mortality, often related to associated co-morbidities and the deleterious effects on the cardio-respiratory system of nasal packing and bed rest. 31,32 This difficult problem has been rendered even more difficult by the rise in prescriptions for anticoagulant agents, 33 particularly the newer oral anticoagulants (‘NOACs’).…”
Section: Nose Bleedsmentioning
confidence: 99%